Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1080/14786419.2019.1579808
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the bioactive flavonoids isolated from Azadirachta indica

Abstract: Two novel natural metabolites, 3-O-butyl-(-)-epicatechin (1) and 3-O-butyl-(-)epigallocatechin (2), as well as several known substances, (-)-epicatechin (3), (+)gallocatechin (4), (-)-epigallocatechin (5), azadirachtin A (6), trilinolein (7) and octadecanoic acid-tetrahydrofuran-3,4-diyl ester (8), were isolated from the bark of Azadirachta indica. The structures of all compounds were established by comprehensive and comparative spectroscopic analysis of NMR and ESI-HRMS data. The new metabolites 1 and 2 repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…In effect, lipophilicity is one of the most important physical properties in drug discovery, since it intervenes in the pharmacodynamics, pharmacokinetics, and toxicity of many compounds (43) . For example, Echeverría et al (44) and Cen-Pacheco et al (24) reported that the bactericide and acaricidal activity of the flavonoids is associated with a narrow range of lipophilicity values (LogP between 1.5 and 3.0).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In effect, lipophilicity is one of the most important physical properties in drug discovery, since it intervenes in the pharmacodynamics, pharmacokinetics, and toxicity of many compounds (43) . For example, Echeverría et al (44) and Cen-Pacheco et al (24) reported that the bactericide and acaricidal activity of the flavonoids is associated with a narrow range of lipophilicity values (LogP between 1.5 and 3.0).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, compounds 1-11 were tested at a concentration of 6 mM. The final volume used in the larval immersion test was 750 μL, whereas in the adult immersion test it was 5 mL (24) .…”
Section: Concentration Of the Tested Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the powdered leaves are combined with water and used to treat freckles on the face, increase hunger by reducing stomach gas production and eradicating intestinal worms [21]. Te bioactive favonoids were isolated from neem tree bark and were tested for acaricidal activity with a LD50 value less than 7.2 mM [22]. Apart from medicinal applications, the neem parts are also tested for its insecticidal property [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal potential of the tree can be attributed to various diverse nature of secondary metabolites/bioactives, that is, terpenes [13], limonoids [14], flavonoids [15], alkaloids [16], and saponins [17], which mediated their role by affecting various biological processes.…”
Section: Introductionmentioning
confidence: 99%